Elektrochemisches Verhalten von Lithium-Schwefel-Zellen mit unterschiedlicher Kathodenstruktur - Scherr, Christopher (KIT Scientific Publishing, 2014)
The storage of energy is one main bottle-neck of the german energy transition. The lithium-sulfur battery with its high theoretical specific values can here play a major role. Depending on the composition and production of the cathode, the electrochemical characteristics of the battery vary greatly. In this work, the influence of the cathode structure and composition was analysed in terms of capacity and lifetime of lithium-sulfur cells.
German
Keywords: Lithium-Schwefel-Akkumulator; Li-S Akkumulatorlithium-sulfur-battery; Lithium-Schwefel-Batterie; Schwefel; sulfur; Kathode; cathode; li-s battery